2000
DOI: 10.1002/1097-4636(20000915)51:4<726::aid-jbm22>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-deficient hydroxyapatite-PLGA composites: Mechanical and microstructural investigation

Abstract: The microstructural and mechanical properties of composites composed of calcium deficient hydroxyapatite (CDHAp) and poly(lactide-co-glycolide) (PLGA) have been investigated. The composites were formed by hydrolysis of alpha-tricalcium phosphate (alpha-TCP) to CDHAp in pressed precomposite compacts of alpha-TCP-PLGA-NaCl. The differences in hydrolysis of alpha-TCP-PLGA-NaCl for two compositions of 80:10:10 wt % and 60:20:20 wt %. were monitored by isothermal calorimetry and X-ray diffraction. The microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…An interesting list of references assigned to the different ways of preparing HA/ poly(α-hydroxyesters) biodegradable composites might be found in publications by Durucan and Brown. 53,393,394 The authors prepared CDHA/PLA and CDHA/PLGA biocomposites using a solvent casting technique with a subsequent hydrolysis of α-TCP to CDHA in aqueous solutions. The presence of both polymers was found to inhibit α-TCP hydrolysis compared with that of single-phase α-TCP alone; what's more, the inhibiting effect of PLA exceeded that of PLGA.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…An interesting list of references assigned to the different ways of preparing HA/ poly(α-hydroxyesters) biodegradable composites might be found in publications by Durucan and Brown. 53,393,394 The authors prepared CDHA/PLA and CDHA/PLGA biocomposites using a solvent casting technique with a subsequent hydrolysis of α-TCP to CDHA in aqueous solutions. The presence of both polymers was found to inhibit α-TCP hydrolysis compared with that of single-phase α-TCP alone; what's more, the inhibiting effect of PLA exceeded that of PLGA.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…More complex carbonated-FA/PLA porous biocomposite scaffolds are also known [323]. An interesting list of references, assigned to the different ways of preparing HA/poly(a-hydroxyesters) biodegradable composites, might be found in publications by Durucan and Brown [49,324,325]. The authors prepared CDHA/PLA and CDHA/PLGA composites by solvent casting technique with a subsequent hydrolysis of a-TCP to CDHA in aqueous solutions.…”
Section: Apatite-based Biocompositesmentioning
confidence: 99%
“…The authors prepared CDHA/PLA and CDHA/PLGA composites by solvent casting technique with a subsequent hydrolysis of a-TCP to CDHA in aqueous solutions. The presence of both polymers was found to inhibit a-TCP hydrolysis, if compared with that of single-phase a-TCP; what is more, the inhibiting effect of PLA exceeded that of PLGA [49,324,325]. The physical interactions between calcium orthophosphates and poly(ahydroxyesters) might be easily seen in Fig.…”
Section: Apatite-based Biocompositesmentioning
confidence: 99%
“…Previous studies investigating the use of α-TCP in composites with polymers have indicated that it improved the dissolution properties and enhanced bone formation [6][7][8][9][10] . In an attempt to reduce the dissolution rate of α-TCP by coating it with an organic polymer, Kitamura et al 11) found that a hydroxypropyl cellulose (HPC) coating was effective in controlling bioresorption and improving α-TCP workability.…”
Section: Introductionmentioning
confidence: 99%